Cecal Volvulus. Issue 1 (4th May 2022) - Di Dier, Kelly; De Backer, Adelard; Vanhoenacker, Filip
Teaching Point: The coffee bean sign, the whirl sign, and the bird's beak sign are the key findings on abdominal CT of cecal volvulus.